Kajian ciri-ciri pasir pengalas dan pengisi sambungan turapan blok konkrit saling mengunci - Nur Izzi Md. Yusoff,; Amiruddin Ismail,; Rosli Hainin,; Hasanan Md. Nor,; Khairul Anwar Husin, (2009)
The use of interlocking concrete block pavement as a road surface has increased in the road construction recently. This study was conducted to envisage the problems occur particularly for the bedding and joint filling sand of the interlocking concrete block pavement. Moreover, the effect of the moisture on the bedding sand was also studied. Two type of additives namely as palm oil fly ash (POFA) and silica fume, which carry the pozzolanic behaviour, were mixed with joint filling sand in order to improve its quality. These materials are industrial waste compound which can be easily found in Malaysia. Two types of permeability experiments, the constant and falling head tests were conducted to evaluate the permeability of the joint filling sands with the percentage additives used of 2%, 4%, 6%, 8% and 10%. A physical model was developed to investigate the degree of compaction and water absorption via sand in joints. Water absorption test was also conducted onto the model with the addition of additives of 0%, 5% and 10% with the joint filling sand for 5 and 10 days. Study shown that the incorporation of additives reduced the permeability of joint filling sand with the optimum values obtained for both POFA and silica fume mixtures both were at 2% respectively.